Pelatihan Pembuatan Presentasi Interaktif Menggunakan Canva untuk Optimalisasi Pembelajaran Siswa SMKN 8 Semarang - Setiarso, Galih; Handayani, Sri; Christanto , Febrian Wahyu (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
Community Service by the Faculty of Information and Communication Technology (FTIK) of Semarang University (USM) aims to provide training to students on optimizing the use of the Canva application as a tool for designing interesting and interactive learning materials. The activity method through training which was carried out on Friday, October 18, 2024 was attended by 19 class XII students of the TKJ Department of SMK N 8 Semarang. The results of this activity were measured from the results of the pre-test and post-test, it was obtained that 100% of participants felt helped after participating in the training where students' knowledge and understanding in making designs and presentations with Canva became deeper.